Avaliação da temperatura de transição vítrea em nanocompósitos de epóxi com nanotubos de carbono, óxido de grafeno e carbonato de cálcio - Natália Fernandes Perdigão (2021)
The glass transition (Tg) of epoxy-based systems is its main thermal event, associated both with the structure of the material and its range of application. Variations in epoxy nanocomposites Tg have been presented in the scientific literature with a very large variability of values. In this work, four types of nanocomposite systems were produced, each one with a different nanomaterial (oxidized carbon nanotube, amine carbon nanotube, graphene oxide and calcium carbonate) at concentration of 1% w/w. The focus of the study of the nanocomposites was to obtain the maximum glass transition temperature from the variation of weight hardener per 100 parts by weight of resin (Phr). For this purpose, Differential Scanning Calorimetry (DSC) and Dynamic Mechanical Analysis (DMA) were used. These analyses also allowed to investigate other important thermomechanical properties of nanocomposites. Complementary water wetability and Scanning Electron Microscopy (SEM) characterizations were also performed on these systems. A statistical analysis was performed on DSC, DMA and wetability results. Furthermore, DSC and DMA results showed that no change in the maximum glass transition value occurred for the nanocomposites in relation to the reference (without additives). Also, no change was observed for the Tg onset and ΔHreaction properties, but a possibility of linearizing data from Tg, Tg onset and ΔHreaction to find an ideal Phr was confirmed. By DSC, it was observed the possibility of a slight reduction of ideal Phr for the nano-CaCO3 nanocomposite and a slight increase for the NTC-Amine nanocomposite. By DMA, the 30°C storage module increased for NTC-Ox and GO based nanocomposites, with increases of up to 5.5% and 5.4%, while for the 160°C storage module this increase was up to 12.5% for the GO nanocomposite. The water wettability test at Phr 19,5 showed an increase in hydrophobicity of up to 52.5° in relation to the reference for the nanocomposite of nanometric calcium carbonate.